2007
DOI: 10.1017/s0020818307070178
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Income Inequality in Mexico, 1990–2000

Abstract: In this article we explore the relationship between the investments of multinational corporations~foreign direct investment! and income inequality in Mex-ico+ We argue that Mexico's liberalization of foreign direct investment~FDI! inflows in the 1990s provides a natural experiment to test how FDI affects income inequality in a middle-income country+ We use an instrumental variables approach as our identification strategy to mitigate problems of endogeneity and omitted variable bias+ In an empirical test of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 24 publications
10
93
0
3
Order By: Relevance
“…Wei et al (2009) blamed the uneven distribution of FDI (rather than FDI itself) to be the cause of rising regional inequality in China. Jensen and Guillermo (2007) revealed a decrease in income inequality in Mexico with FDI inflows whereas Mah (2003) found no significant effect for Korea. Blonigen and Slaughter (2001) failed to find any significant effects of FDI on wage inequality between skilled and unskilled workers in the United States.…”
Section: Foreign Direct Investment and Income Distributionmentioning
confidence: 90%
“…Wei et al (2009) blamed the uneven distribution of FDI (rather than FDI itself) to be the cause of rising regional inequality in China. Jensen and Guillermo (2007) revealed a decrease in income inequality in Mexico with FDI inflows whereas Mah (2003) found no significant effect for Korea. Blonigen and Slaughter (2001) failed to find any significant effects of FDI on wage inequality between skilled and unskilled workers in the United States.…”
Section: Foreign Direct Investment and Income Distributionmentioning
confidence: 90%
“…Jensen and Rosas (2007) suggest two channels through which this investment might affect inequality. First, fdi brings capital into a country, thus reducing the total returns to capital and increasing the returns to labour.…”
Section: Foreign Direct Investment (Fdi) and Income Inequalitymentioning
confidence: 99%
“…Blanton and Blanton (2007) found that foreign investors prefer countries with welltrained and skilled labour with a low cost of wages, while Jensen and Rosas (2007) conducted research in Mexico and found that FDI and wages are positively significant. Mexico is among the fast-emerging countries where labour rate is still very low relative to other emerging countries and therefore it could still attract foreign investments into the country with increasing wage rates.…”
Section: Macroeconomic Fundamentalsmentioning
confidence: 99%